Cape fear - Daniel, Rob (Liverpool : Auteur, an imprint of Liverpool University Press, 2021)
Martin Scorsese's Cape Fear (1991) opens with a shot of water and climaxes on a raging river. Despite, or perhaps because of, the film's great success, critical analysis of the film typically does not delve beneath the surface of Scorsese's first major hit. As it reaches its 30th anniversary, Cape Fear is now ripe for a full appraisal.
JSTOR
Keywords: Cape Fear (Motion picture : 1991); Cape Fear (Motion picture : 1991); Horror films -- History and criticism; Films d'horreur -- Histoire et critique; Horror films; horror; US cinema; Criticism, interpretation, etc